How efficient are Indian banks in managing the risk-return trade-off? An empirical analysis - Jalaludeen Navas; Periyasamy Dhanavanthan; Daniel Lazar (Risks, 2020)
Risk taking is an inherent element of the banking business. Banks make conscious decisions regarding risk taking as they expect to make more return if they take more risk. The primary objective of this study is to empirically investigate the efficiency of Indian banks in generating return relative to the risk they take. If the efficiency measurement is not adjusted for different risk preferences, then a bank earning lower return at lower risk may be misclassified as less efficient compared to peers earning the same level of return, but operating at a higher level of risk. This paper uses measures of liquidity risk, credit risk, market risk, and insolvency risk to develop a risk-return stochastic frontier in order to examine the risk efficiency of banks, a novel attempt in the Indian context. The paper further analyzes the efficiency of banks with respect to bank specific characteristics and risk management regimes. The models are estimated using data from a sample of 47 major banks for the period 2009-2018. The study reveals that Indian banks, on average, exhibited lower efficiency in trading risk against return during the sample period.
Keywords: 330; risk management; efficiency; stochastic frontier; technical efficiency